Genetic connectivity and self-replenishment of inshore and offshore populations of the endemic anemonefish, Amphiprion latezonatus - Steinberg, R.; van der Meer, M.; Walker, E.; Berumen, M.; Hobbs, Jean-Paul; van Herwerden, L. (Springer Verlag, 2016)
Globally, marine species are under increasing pressure from human activities, including ocean warming, acidification, pollution, and overfishing. Species most vulnerable to these pressures tend to be ecological specialists that have low abundance and small distribution ranges (endemics). Marine endemics often exist as meta-populations distributed among few isolated locations. Determining genetic connectivity among these locations is essential to understanding the recovery potential of endemics after local extinction events. This study examined connectivity in the endemic anemonefish, Amphiprion latezonatus, a habitat specialist with low abundance at most locations. Evolutionary and contemporary migration, genetic diversity, and self-replenishment among the four main locations (Sunshine Coast, North Solitary Island, Lord Howe Island, and Norfolk Island) that comprise the entire A. latezonatus geographic range were assessed using mtDNA and microsatellite markers. Though historical gene flow inferred from mtDNA appeared high, population genetic differentiation was evident and contemporary gene flow inferred from microsatellites was limited, alongside very high (=89 %) self-replenishment at all locations. Together, these data suggest prolonged recovery times following severe population decline (or extirpation) and indicate a need to protect this species at all locations, particularly Norfolk Island and Sunshine Coast where marine protected areas are lacking.